The characterization of power supply noise for optical mouse sensor - Mohd Khairuddin, Md Arshad; Uda, Hashim; Ming, Choo Chew (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org